1987
DOI: 10.1248/cpb.35.3838
|View full text |Cite
|
Sign up to set email alerts
|

Studies on poisonous metals. XVIII. Effects of several dithiocarbamates on tissue distribution and excretion of cadmium in rats.

Abstract: The effects of various chelating agents, sodium N-benzyl-D-glucamine dithiocarbamate (NBGDTC), sodium N-p-methylbenzyl-D-glucamine dithiocarbamate (NMBGDTC), and sodium N-p-isopropylbenzyl-D-glucamine dithiocarbamate (NPBGDTC), which were newly synthesized, sodium N-methyl-D-glucamine dithiocarbamate (NMGDTC), diethyldithiocarbamate (DEDTC),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…DDTC seems to have a complexation effect on Cd and Cu. These results are in agreement with the observations of some authors who recognise the use of DDTC as an antidote for Cu toxicity (Grafsträn and Greene, 1980;Kojima et al, 1987).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…DDTC seems to have a complexation effect on Cd and Cu. These results are in agreement with the observations of some authors who recognise the use of DDTC as an antidote for Cu toxicity (Grafsträn and Greene, 1980;Kojima et al, 1987).…”
Section: Resultssupporting
confidence: 93%
“…Synergism and antagonism phenomena can appear and thus greatly contradict the results obtained when evaluations are conducted with single toxicants only (Kojima et al, 1987;Pommery et al, 1987;Robert, 1984). These results confirm the difficulty to evaluate the true toxicity of a compound in the natural medium which is highly complex by definition.…”
Section: Resultsmentioning
confidence: 97%
“…The corresponding 4-methylbenzyl and 4-isopropylbenzyl compounds were also quite effective (33). The application of the Topliss procedure to this series of compounds, with a planned range of substitutions on the benzene ring, showed that of the 4-Cl, 4-CH30, 4-CH3, 3-CF3 derivatives and the parent compound, the 4-CH30 was significantly superior to all of the others on the basis of reductions it effected in both renal and hepatic cadmium levels (34).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests the n parameter of Hansch and Leo (32), though a number of related parameters have served in the same fashion (33,34). The correlation of relative cadmium levels in the liver and kidney following a standard chelate treatment has been examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation